Zinc import mediated by AdcABC is critical for colonization of the dental biofilm by Streptococcus mutans in an animal model. (10th May 2021) - Ganguly, T.; Peterson, A.M.; Kajfasz, J.K.; Abranches, J.; Lemos, J.A.
Abstract: Trace metals are essential to all domains of life but toxic when found at high concentrations. Although the importance of iron in host–pathogen interactions is firmly established, contemporary studies indicate that other trace metals, including manganese and zinc, are also critical to the infectious process. In this study, we sought to identify and characterize the zinc uptake system(s) of Streptococcus mutans, a keystone pathogen in dental caries and a causative agent of bacterial endocarditis. Different than other pathogenic bacteria, including several streptococci, that encode multiple zinc import systems, bioinformatic analysis indicated that the S. mutans core genome encodes a single, highly conserved, zinc importer commonly known as AdcABC. Inactivation of the genes coding for the metal‐binding AdcA (Δ adcA ) or both AdcC ATPase and AdcB permease (Δ adcCB ) severely impaired the ability of S. mutans to grow under zinc‐depleted conditions. Intracellular metal quantifications revealed that both mutants accumulated less zinc when grown in the presence of a subinhibitory concentration of a zinc‐specific chelator. Notably, the Δ adcCB strain displayed a severe colonization defect in a rat oral infection model. Both Δ adc strains were hypersensitive to high concentrations of manganese, showed reduced peroxide tolerance, and formed less biofilm in sucrose‐containing media when cultivated in the presence of the lowest amount of zinc that support their growth, but not when zinc was supplied in excess. Collectively, this study identifies AdcABC as the major high affinity zinc importer of S. mutans and provides preliminary evidence that zinc is a growth‐limiting factor within the dental biofilm. Abstract : Streptococcus mutans encodes a high affinity ABC‐type zinc transporter AdcABC. Deletion of either metal binding protein AdcA or permease complex forming proteins AdcC and AdcB dysregulates metal homeostasis. In both zinc deplete or replete medium, the wild‐type strain maintains intracellular zinc:manganese ratio homeostasis. However, Zn transport mutant strains, while the adc mutants can maintain zinc:manganese ratio under zinc replete conditions, likely through the activity of an uncharacterized low affinity transporter, the zinc:manganese ratio is severely tilted towards manganese in zinc restricted conditions. Deletion of the adcABC genes impairs oxidative stress tolerance and biofilm formation under zinc‐restricted condition and tooth colonization of in a rat model. Graph created with BioRender.com.